Preload & Frank-Starling curves, from textbook to bedside: clinically applicable non-additionally invasive model-based estimation in pigs - Smith, R; Chase, JG; Pretty, CG; Davidson, S; Shaw, GM; Desaive, T (Elsevier, 2021)
Background Determining physiological mechanisms leading to circulatory failure can be challenging, contributing to the difficulties in delivering effective hemodynamic management in critical care. Continuous, non-additionally invasive monitoring of preload changes, and assessment of contractility from Frank-Starling curves could potentially make it much easier to diagnose and manage circulatory failure.